2012
DOI: 10.1007/bf03262861
|View full text |Cite
|
Sign up to set email alerts
|

Effect of consuming different dairy products on calcium, phosphorus and pH levels of human dental plaque: A comparative study

Abstract: Cheese and yogurt without any added sugar (sucrose) are non-cariogenic and to some extent cariostatic as they increase calcium and phosphorus concentration in dental plaque. Dairy products without added sugar can be recommended as after meal desserts, especially to school children, which would help to reduce the incidence of dental caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 25 publications
1
25
0
2
Order By: Relevance
“…mutans colonization triggered the evaluation of caries by milk intake. Experimental studies have suggested that milk and milk components have cariostatic properties through pH neutralization [ 40 ], supersaturation of calcium and phosphate in the tooth interphase [ 41 , 42 , 43 ], and effects on bacteria, but observational studies are inconsistent [ 44 ]. Based on these traits combined with our finding of less S .…”
Section: Discussionmentioning
confidence: 99%
“…mutans colonization triggered the evaluation of caries by milk intake. Experimental studies have suggested that milk and milk components have cariostatic properties through pH neutralization [ 40 ], supersaturation of calcium and phosphate in the tooth interphase [ 41 , 42 , 43 ], and effects on bacteria, but observational studies are inconsistent [ 44 ]. Based on these traits combined with our finding of less S .…”
Section: Discussionmentioning
confidence: 99%
“…Prior research clearly showed that patients’ diet–related behavior is integrally related to their oral health 1–16 . Educating future dental care providers about these issues is therefore important, especially because a survey with practicing dentists found that these providers indicated they would be more interested in educating their patients about diet–related behavior change if empirical evidence supported a relationship between obesity and oral health 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Diet–related behavior can also be protective as shown by Kolker et al, who found that higher milk consumption was associated with lower caries rates 5 . Other studies have reported that dairy products with no added sugar had cariostatic effects 6 , 7 and even contributed to preventing caries and periodontal disease 8–10 . While the evidence is limited concerning the relationship between the frequency of consuming meat and oral health, Laffranchi et al found greater demineralization and more white spot lesions in adult vegans compared to adults with no dietary restrictions, 11 and Sherfudhin et al reported in their study with young adult Indian vegetarians that they had a higher degree of tooth wear, higher crowding, and other poor oral health effects compared to non–vegetarian subjects 12 .…”
mentioning
confidence: 97%
“…Ayrıca, diş çürüğü görülme sıklığının azaltılması için özellikle okul çocuklarına tatlı yedikten sonra, şeker içermeyen süt ürünlerinin tüketiminin önerilebileceği sonucuna varılmıştır. 55 Yapılan çalışmalar, yoğurt içinde bulunan CPP'lerin demineralizasyon üzerinde inhibe edici bir etkiye sahip olduğunu ve diş minesinin remineralizasyonunu teşvik ettiğini göstermektedir. 53 Diş çürüğünün oluşmasının önlenmesinde daha sık diş fırçalamanın yanında, yemeklerde daha çok süt ve süt ürünü tüketimi ve tatlandırılmış tahıl tüketiminden kaçınılması önerilebilmektedir.…”
Section: Süt üRünleri̇ Ve Di̇ş çüRüğüunclassified